Reliability and Validity of the Adapted Chinese Dispositional Flow Scale-2 in Leisure-time Runners - Yang, Lijuan; Menon, Rajitha (The Journal of Behavioral Science, 2022)
The dispositional flow in leisure-time runners may contribute to their long-term commitment to running. The existing Chinese translation of the Dispositional Flow Scale–2 (DFS-2) has poor psychometric properties, such as inadequate internal consistency. Therefore, the first objective of the study was to translate the DFS-2 into Chinese. The second objective was to validate it among leisure-time runners. Runners were recruited from several community leisure-time running groups in Guangzhou city in China. Three stages of analysis were conducted to achieve the second objective. In the first stage, an exploratory factor analysis was conducted on data obtained from 386 Chinese leisure-time runners (51% men). In the second stage, the analysis was performed on another sample of 534 Chinese leisure-time runners (55.5% men). A confirmatory factor analysis, an internal consistency evaluation, and an item analysis were conducted. A test-retest reliability assessment was conducted on 41 Chinese leisure-time runners (43.9% men) in the third stage. The internal consistency of the scale was excellent (α = .95). A positive and significant correlation (p < .001) was found among nine factors of flow and harmonious passion. Additionally, an excellent intraclass correlation coefficient (ICC) in the overall scale was found after a 2-week time period (ICC = .92, p < .001, 95%, CI = .84 to .96). The findings contribute to behavioral science by providing a reliable scale to measure the subjective tendency to experience flow in leisure-time activities. This can be used to promote physical activity by health educators.